Influence of seasonal and environmental patterns on the lipid content and fatty acid profiles in gonads of the edible sea urchin Paracentrotus lividus from Sardinia. (February 2016) - Siliani, Silvia; Melis, Riccardo; Loi, Barbara; Guala, Ivan; Baroli, Maura; Sanna, Roberta; Uzzau, Sergio; Roggio, Tonina; Addis, Maria Filippa; Anedda, Roberto
Abstract: The influence of seasonal and environmental patterns on the lipid fraction of Paracentrotus lividus gonads was investigated. For this purpose, sea urchins were collected monthly over a year from two Sardinian coastal areas. Total lipids in gonads follow an annual cyclical trend, described by a sine wave curve, that it is more influenced by season than by growing area. The lowest lipid content in gonads corresponds to a high percentage of mature reproductive stages (i.e. winter season), independently of sampling area. A variation in total lipid content follows a change in photoperiod, while it is related to sea surface temperature. Multivariate analysis on fatty acid profiles of gonads, detected by gas chromatography, clusters the collected specimens mainly according to the sampling area, secondly according to the sites within the same sampling area and finally according to season. Graphical abstract: Highlights: Lipid content in sea urchin gonads is more influenced by season than by growing area. Total lipids follow an annual cyclical trend described by a sine–wave curve. Lipid content is minimum during the premature and mature reproductive stages. Essential fatty acids (EPA and ARA) are mainly discriminant for season. Monounsaturated fatty acids are mainly discriminant for collection area.